Dependence of Pyroelectric Properties of La0.03Sr0.255Ba0.7Nb2-yTiyO(6-y/2) Ceramic on Electric Field, Grain Refinement and Ti/Nb Crystallite Sizes - Gan, W.C.; Abd Majid, Wan Haliza (Penerbit Universiti Kebangsaan Malaysia, 2010)
The pyroelectric properties of La0.03Sr0.255Ba0.7Nb2-yTiyO(6-y/2) (LSBNT) ceramic pellets using several Ti/Nb ratios sintered at 1250 degrees C for 5 h were investigated. The samples were subjected to several values of electric fields in order to obtain the optimum electric field strength. The pyroelectric coefficients, (p) were measured using the quasi-static method by applying several heating rates. The results show that the Ti/Nb ratios and the dc poling field, (E-dc) influenced the measured pyroelectric coefficient of the LSBNT ceramic pellets. The mean grain size of the particles as obtained from scanning electron microscope (SEM) does not seem to give significant impact on the pyroelectric coefficient of the ceramic pellets. However, the X-Ray diffraction (XRD) results indicate that the crystallite sizes of Ti and Nb of these ceramic pellets after being treated with sintering process also influence the measured pyroelectric coefficients of the ceramic pellets.